PELATIHAN DAN PENDAMPINGAN PRAKTIKUM MIKROBIOLOGI BAGI SISWA DAN GURU BIOLOGI TINGKAT SMA, KABUPATEN TOBA - Berlian Simanjuntak; Roga Florida Kembaren; Merry Meryam Martgrita; Chintya Sinar Lumbantoruan; FBA Fitriani; Theodora M Putri; Adrianto Prihartantyo; Yulisa Lestari; Juli Yanti Damanik; Andrew Rolas Siagian; Endang Sibarani; Bastian Jose Habeahan; Reni Tamba; Ketty Tambunan; Elsa Pangaribuan; Gabriele Siagian (Jurnal Abdi Insani, 2026)
The training and mentoring of microorganism isolation and identification practicums wereconducted as an effort to provide learning integration experiences with practicum activitiesdue to the limited laboratory facilities in high schools in Toba Regency. The community serviceactivities began with an evaluation of initial understanding related to the community serviceactivities carried out, followed by the provision of basic theory on microorganism isolation andidentification. After that continued with practical activities of isolation and identification ofmicroorganisms carried out through aseptic techniques and mentoring in observations, datarecording, and analysis of practical observation results. The activity was concluded with a finalevaluation of the activity. Training and mentoring were carried out intensively so the studentsand teachers were able to carry out the stages and analysis of practical activities appropriately.The evaluation results showed that this activity increased the understanding of students andteachers of the basic theory and practical work of isolating and identifying microorganisms for66%. This training activity is also expected to be a strategic step to encourage high schools inToba Regency to have laboratory facilities to support the integration of learning materials withpractical activities.